SEASONAL VARIATION IN THE ESSENTIAL OIL COMPOSITION OF MAJORANA HORTENSIS MOENCH FROM WESTERN GHATS REGION OF SOUTH INDIA. - Mangai, S.Alarmal; Subban, Ravi (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To evaluate the seasonal variation in the composition of essential oil of Majorana hortensis Moench from Western Ghats region of South India during summer and winter seasons and to find out the chemo type of oil. Method: The essential oil from the plant is extracted by hydro distillation method using Clevenger type apparatus. The compounds are analysed by GC-MS method and identified by NIST library verification. Â Results: Winter season oil contains trans-sabinene hydrate along with other constituents in considerable quantity whereas in summer season oil, terpinen-4-ol is the predominant constituent. Conclusion: Winter season is suitable for oil production in Western Ghats region of South India. The winter seasonal oil belongs to sabinene hydrate/terpinen-4-ol chemo type which is more fragrant than summer seasonal oil. On comparison with the literature datas, it has been found that the chemo type of the oil is similar to that of Egyptian oil in both summer and winter seasons. Keywords: : Majorana hortensis Moench, GC-MS, Trans-Sabinene hydrate, Terpene-4-ol.